Corrosion-resistant pipe support and method of making same
By introducing aminosilane-modified mica powder, composite corrosion inhibitor powder, and a combination of hydrophobically modified nano-silica and flake talc powder into the epoxy resin coating, a multi-layer protective system is formed, which solves the corrosion problem of epoxy resin coating in humid air and corrosive media environments, and achieves improved corrosion resistance and safety assurance.
Patent Information
- Application Number
- CN202610997771.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-06
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-07-06
AI Technical Summary
Existing epoxy resin coatings cannot effectively prevent the penetration of corrosive media such as moisture, oxygen, and chloride ions during long-term service, causing steel pipe supports to corrode in humid air and corrosive media environments, affecting load-bearing capacity and safety.
Aminosilane-modified mica powder, composite corrosion-inhibiting powder, and hydrophobically modified nano-silica are mixed with flake talc powder and epoxy resin to form a layered physical barrier and chemical corrosion inhibition protection. Through the synergistic effect of zinc phosphate, montmorillonite, and hexadecyltrimethylammonium bromide, passive barrier and active corrosion inhibition functions are provided. Furthermore, the nano-silica and talc powder form a progressively transitioning overlapping network to prevent delamination and sedimentation.
It significantly extends the penetration path of corrosive media, provides a uniform physical barrier and chemical corrosion inhibition protection, improves the corrosion resistance of the coating, prevents the expansion of local defects, and ensures the stability and safety of the coating during its service life.
Smart Images

Figure CN122628634B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of pipe support coating protection technology, specifically to a corrosion-resistant pipe support and its preparation method. Background Technology
[0002] Pipe supports, as key supporting components in pipeline systems that bear the weight of the pipeline itself and the medium, and guide the thermal displacement of the pipeline, are widely used in industries such as petrochemicals, power energy, and coastal engineering. During actual service, pipe supports are exposed to corrosive media such as humid air, salt spray, acid mist, and oil and gas volatiles for extended periods. Once the steel pipe support substrate corrodes, not only will its load-bearing capacity be weakened, but it may also lead to pipeline misalignment, leakage, and other safety accidents due to support failure. Therefore, applying an anti-corrosion coating to the surface of the pipe support and improving the coating's corrosion resistance is an important technical means to ensure the long-term safe operation of the pipeline system. Epoxy resin, due to its excellent adhesion, chemical resistance, and mechanical strength, is one of the most commonly used base resins for anti-corrosion coatings of pipe supports. However, during long-term service, pure epoxy resin coatings inevitably contain defects such as micropores and free volume in their cured network. Corrosive media such as moisture, oxygen, and chloride ions can still gradually penetrate to the surface of the metal substrate through these channels, making it difficult for the coating's long-term corrosion resistance to meet the protection requirements of harsh corrosive environments. Summary of the Invention
[0003] The purpose of this invention is to provide a corrosion-resistant pipe support and its preparation method to solve the technical problems mentioned in the background art.
[0004] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a corrosion-resistant pipe support includes the following steps: (1) React mica powder with an aminosilane coupling agent to obtain aminosilane modified mica powder; (2) Disperse montmorillonite in a solvent, and simultaneously add zinc salt solution and phosphate solution to carry out in-situ precipitation reaction. Then add cationic surfactant to carry out reaction to obtain composite corrosion inhibitor powder; (3) React nano-silica with a hydrophobic silane coupling agent to obtain hydrophobic modified nano-silica; (4) The hydrophobically modified nano-silica is mixed with flake talc to obtain a composite thixotropic component; (5) The aminosilane-modified mica powder, the composite corrosion inhibitor powder, the composite thixotropic component and epoxy resin are mixed to form component A. Component B containing curing agent is mixed with component A and coated on the surface of the pipe support substrate and cured to obtain the corrosion-resistant pipe support.
[0005] Preferably, the aminosilane coupling agent in step (1) is aminosilane coupling agent KH-792; the reaction temperature is controlled at 55-65℃; and the mica powder has a flake diameter of 15-25μm.
[0006] Preferably, the mass ratio of mica powder to aminosilane coupling agent is 10:(0.1-0.5).
[0007] Preferably, the zinc salt solution in step (2) is a zinc nitrate solution, the phosphate solution is a disodium hydrogen phosphate solution, the cationic surfactant includes hexadecyltrimethylammonium bromide, and the montmorillonite flakes have a diameter of 5-15 μm.
[0008] Preferably, during the simultaneous addition of the zinc salt solution and the phosphate solution, the molar ratio of zinc ions to phosphate is controlled at 3:2, and the pH of the reaction system is adjusted to 5.5-6.5 during the dropwise addition.
[0009] Preferably, the hydrophobic silane coupling agent in step (3) is octyltrimethoxysilane; the reaction temperature is controlled at 60-70°C, and the nano-silica particle size is 20-40 nm. The mass ratio of the nano-silica to octyltrimethoxysilane is 10:(0.8-1.2).
[0010] Preferably, step (4) specifically includes adding the hydrophobically modified nano-silica and the flake talc powder to a butyl glycidyl ether resin diluent and dispersing them evenly to obtain the composite thixotropic component; The flaky talc powder has a flake diameter of 1–5 μm; the mass ratio of the hydrophobically modified nano-silica to the flaky talc powder is 1:(1–2).
[0011] Preferably, in step (5), the raw material ratio of component A by mass includes: 100 parts epoxy resin, 10-15 parts aminosilane modified mica powder, 3-6 parts of the composite corrosion inhibitor powder, and 10-15 parts of the composite thixotropic component.
[0012] Preferably, component A in step (5) further includes 0.1 to 0.5 parts of defoamer and 0.1 to 0.8 parts of leveling agent; before coating the surface of the pipe support substrate, a pretreatment step of removing rust and / or oil from the surface of the pipe support substrate is also included.
[0013] A corrosion-resistant pipe support is prepared by the method described above. Compared with the prior art, the beneficial effects of the present invention are: 1. Mica powder surface-treated with an aminosilane coupling agent allows its flaky particles to align in the coating, forming a layered, tortuous physical barrier. This significantly extends the penetration path of corrosive media such as water, oxygen, and salt spray to the metal substrate, slowing down the corrosion rate at its source. Simultaneously, a composite corrosion-inhibiting powder composed of zinc phosphate, montmorillonite, and cetyltrimethylammonium bromide achieves chemical slow release and passivation: zinc phosphate provides zinc and phosphate ions as the active source of corrosion inhibition; layered montmorillonite acts as a supporting framework, limiting the dissolution and diffusion of zinc phosphate through physical barriers and narrow interlayer channels; and CTAB intercalation widens the interlayer spacing and creates a hydrophobic environment, further delaying moisture intrusion and ion dissolution. The synergistic effect of these three components allows for the slow and controlled release of zinc phosphate throughout its service life. When corrosive media penetrates, the released zinc ions form zinc hydroxide deposits in the cathodic region, inhibiting the oxygen reduction reaction. Phosphate ions react with iron and zinc ions in the anodic region, forming a dense passivation protective film mainly composed of phosphate and zinc salts, thus providing dual corrosion inhibition functions of cathodic and anodic passivation. Furthermore, when the coating develops microcracks or pinholes due to external forces, the penetrated moisture can still promote the continuous release of ions from adjacent composite powders, causing them to redeposit in situ at the exposed substrate defects. This provides a certain degree of corrosion inhibition and repair at the coating defects, inhibiting the spread of corrosion from the defect points and compensating for the shortcomings of purely physical shielding at damaged areas. Therefore, the coating is upgraded from a simple passive barrier to a protective system that combines passive barrier, active corrosion inhibition, and defect repair.
[0014] 2. To address the uneven stratification caused by the heavy and sinking nature of flake mica powder and the light and floating nature of fine composite corrosion-inhibiting powders, this invention incorporates both hydrophobically modified nano-silica and fine-particle-size flake talc. A tiered, interconnected network is constructed using particle size differences: the smallest nano-silica particles first overlap to form a loose framework, while the medium-sized talc acts as a transitional bridge, overlapping at one end with the nano-silica framework and, at the other end, using its own flake structure, overlapping and frictionally resisting the larger mica flakes and corrosion-inhibiting composite powders. This tiered, interconnected framework structure can stably support particles of varying weights during coating mixing and application, preventing them from settling and separating due to differences in density and size. Ultimately, the shielding pigment and the corrosion-inhibiting pigment can coexist evenly in every area of the coating, ensuring that the two anti-corrosion mechanisms of physical barrier and slow-release repair always work together, eliminating weak links in protection caused by raw material settling, and giving the coating more balanced, durable and stable corrosion resistance as a whole. Attached Figure Description
[0015] Figure 1 This is a SEM image of the coating surface formed after the anti-corrosion coating prepared in Example 1 of the present invention is applied. Detailed Implementation
[0016] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0017] Example 1 A method for preparing a corrosion-resistant pipe support includes the following steps: (1) According to the weight parts, 100 parts of anhydrous ethanol and 4 parts of deionized water are mixed evenly, 10 parts of mica powder with a flake diameter of 15-20 μm are added, and after stirring and dispersing evenly, 0.4 parts of aminosilane coupling agent KH-792 are added. The mixture is stirred and reacted at 60℃ for 2h. After the reaction is completed, the mixture is centrifuged at 4000r / min, washed 3 times with anhydrous ethanol, and dried at 80℃ for 4h to obtain aminosilane modified mica powder.
[0018] (2) 10 parts of montmorillonite with a flake diameter of 5-15 μm were dispersed in 150 parts of deionized water. Under stirring conditions at 48°C, 72 parts of 0.5 mol / L zinc nitrate solution and 48 parts of 0.5 mol / L disodium hydrogen phosphate solution were added slowly and synchronously from two dropper ports to the above montmorillonite aqueous dispersion system, so that the molar ratio of zinc ions to phosphate was 3:2. During the droppering process, the pH of the reaction system was adjusted and maintained at 5.5-6.5 with 0.1 mol / L dilute sodium hydroxide solution. After the droppering was completed, the reaction was stirred at 48°C for 1.5 h to obtain zinc phosphate / montmorillonite precipitate loaded slurry. Then, 3.5 parts of hexadecyltrimethylammonium bromide were added to the slurry and the reaction was stirred at 75°C for 2.5 h. The mixture was centrifuged at 4000 r / min, washed with deionized water until the filtrate was neutral, and dried at 90°C for 8 h to obtain composite corrosion inhibitor powder.
[0019] (3) Disperse 10 parts of fumed nano silica with a particle size of 20-40 nm in 160 parts of anhydrous ethanol, add 6 parts of deionized water, stir and disperse evenly, then add 1.1 parts of octyltrimethoxysilane, stir and react at 65 °C for 2.5 h, centrifuge at 5000 r / min, and dry at 100 °C for 3 h to obtain hydrophobic modified nano silica.
[0020] (4) Add 2 parts of the hydrophobic modified nano silica and 3.5 parts of talc with a sheet diameter of 1-5 μm to 10 parts of butyl glycidyl ether resin dilution, and stir and disperse at 1000 r / min for 40 min to obtain a composite thixotropic component.
[0021] (5) Mix 100 parts of bisphenol A type epoxy resin E-51 (epoxy equivalent 190 g / eq), 14 parts of the aminosilane modified mica powder, 5 parts of the composite corrosion inhibitor powder, 14 parts of the composite thixotropic component, 0.4 parts of polyether defoamer and 0.6 parts of polyurethane leveling agent, first disperse at a high speed of 1500 r / min for 30 min, then reduce to 800 r / min and stir for 20 min to obtain component A; 55 parts of modified aliphatic polyamine curing agent (MH-2218, active hydrogen equivalent of 105 g / eq) were stirred evenly to obtain component B; Take a steel pipe support substrate and pre-treat its surface by sandblasting to remove rust and degreasing with anhydrous ethanol. Before coating, prepare and use component A and component B immediately and mix them evenly. Apply the mixture in three coats to the surface of the pre-treated steel pipe support substrate. Before each coat, weigh and mix component A and component B according to the required amount for that coat. Use the mixture within 30 minutes. Control the wet film thickness of each coat to 70 μm and leave a 50-minute interval between coats. After curing at room temperature for 7 days, bake at 60℃ for 3 hours for post-curing to form an anti-corrosion coating and obtain a corrosion-resistant pipe support.
[0022] Example 2 A method for preparing a corrosion-resistant pipe support includes the following steps: (1) According to the weight parts, 100 parts of anhydrous ethanol and 4 parts of deionized water are mixed evenly, 10 parts of mica powder with a flake diameter of 15-20 μm are added, and after stirring and dispersing evenly, 0.2 parts of aminosilane coupling agent KH-792 are added. The mixture is stirred and reacted at 60℃ for 2h. After the reaction is completed, the mixture is centrifuged at 4000r / min, washed 3 times with anhydrous ethanol, and dried at 80℃ for 4h to obtain aminosilane modified mica powder.
[0023] (2) 10 parts of montmorillonite with a flake diameter of 5-15 μm were dispersed in 150 parts of deionized water. Under stirring conditions at 48°C, 72 parts of 0.5 mol / L zinc nitrate solution and 48 parts of 0.5 mol / L disodium hydrogen phosphate solution were added slowly and synchronously from two dropper ports to the above montmorillonite aqueous dispersion system, so that the molar ratio of zinc ions to phosphate was 3:2. During the droppering process, the pH of the reaction system was adjusted and maintained at 5.5-6.5 with 0.1 mol / L dilute sodium hydroxide solution. After the droppering was completed, the reaction was stirred at 48°C for 1.5 h to obtain zinc phosphate / montmorillonite precipitate loaded slurry. Then, 3.5 parts of hexadecyltrimethylammonium bromide were added to the slurry and the reaction was stirred at 75°C for 2.5 h. The mixture was centrifuged at 4000 r / min, washed with deionized water until the filtrate was neutral, and dried at 90°C for 8 h to obtain composite corrosion inhibitor powder.
[0024] (3) Disperse 10 parts of fumed nano silica with a particle size of 20-40 nm in 160 parts of anhydrous ethanol, add 6 parts of deionized water, stir and disperse evenly, then add 0.9 parts of octyltrimethoxysilane, stir and react at 65 °C for 2.5 h, centrifuge at 5000 r / min, and dry at 100 °C for 3 h to obtain hydrophobic modified nano silica.
[0025] (4) Add 2 parts of the hydrophobic modified nano silica and 2.5 parts of talc with a flake diameter of 1-5 μm to 10 parts of butyl glycidyl ether resin dilution, and stir and disperse at 1000 r / min for 40 min to obtain a composite thixotropic component.
[0026] (5) Mix 100 parts of bisphenol A type epoxy resin E-51 (epoxy equivalent 190 g / eq), 11 parts of the aminosilane modified mica powder, 4 parts of the composite corrosion inhibitor powder, 11 parts of the composite thixotropic component, 0.2 parts of polyether defoamer and 0.2 parts of polyurethane leveling agent, first disperse at a high speed of 1500 r / min for 30 min, then reduce to 800 r / min and stir for 20 min to obtain component A; 55 parts of modified aliphatic polyamine curing agent (MH-2218, active hydrogen equivalent of 105 g / eq) were stirred evenly to obtain component B; Take a steel pipe support substrate and pre-treat its surface by sandblasting to remove rust and degreasing with anhydrous ethanol. Before coating, prepare and use component A and component B immediately and mix them evenly. Apply the mixture in three coats to the surface of the pre-treated steel pipe support substrate. Before each coat, weigh and mix component A and component B according to the required amount for that coat. Use the mixture within 30 minutes. Control the wet film thickness of each coat to 70 μm and leave a 50-minute interval between coats. After curing at room temperature for 7 days, bake at 60℃ for 3 hours for post-curing to form an anti-corrosion coating and obtain a corrosion-resistant pipe support.
[0027] Example 3 A method for preparing a corrosion-resistant pipe support includes the following steps: (1) According to the weight parts, 100 parts of anhydrous ethanol and 4 parts of deionized water are mixed evenly, 10 parts of mica powder with a flake diameter of 15-20 μm are added, and after stirring and dispersing evenly, 0.3 parts of aminosilane coupling agent KH-792 are added. The mixture is stirred and reacted at 60℃ for 2h. After the reaction is completed, the mixture is centrifuged at 4000r / min, washed 3 times with anhydrous ethanol, and dried at 80℃ for 4h to obtain aminosilane modified mica powder.
[0028] (2) 10 parts of montmorillonite with a flake diameter of 5-15 μm were dispersed in 150 parts of deionized water. Under stirring conditions at 48°C, 72 parts of 0.5 mol / L zinc nitrate solution and 48 parts of 0.5 mol / L disodium hydrogen phosphate solution were added slowly and synchronously from two dropper ports to the above montmorillonite aqueous dispersion system, so that the molar ratio of zinc ions to phosphate was 3:2. During the droppering process, the pH of the reaction system was adjusted and maintained at 5.5-6.5 with 0.1 mol / L dilute sodium hydroxide solution. After the droppering was completed, the reaction was stirred at 48°C for 1.5 h to obtain zinc phosphate / montmorillonite precipitate loaded slurry. Then, 3.5 parts of hexadecyltrimethylammonium bromide were added to the slurry and the reaction was stirred at 75°C for 2.5 h. The mixture was centrifuged at 4000 r / min, washed with deionized water until the filtrate was neutral, and dried at 90°C for 8 h to obtain composite corrosion inhibitor powder.
[0029] (3) Disperse 10 parts of fumed nano silica with a particle size of 20-40 nm in 160 parts of anhydrous ethanol, add 6 parts of deionized water, stir and disperse evenly, then add 1.0 part of octyltrimethoxysilane, stir and react at 65 °C for 2.5 h, centrifuge at 5000 r / min, and dry at 100 °C for 3 h to obtain hydrophobic modified nano silica.
[0030] (4) Add 2 parts of the hydrophobic modified nano silica and 3 parts of flaky talc powder with a sheet diameter of 1-5 μm to 10 parts of butyl glycidyl ether resin dilution, and stir and disperse at 1000 r / min for 40 min to obtain a composite thixotropic component.
[0031] (5) Mix 100 parts of bisphenol A type epoxy resin E-51 (epoxy equivalent 190 g / eq), 12 parts of the aminosilane modified mica powder, 4.5 parts of the composite corrosion inhibitor powder, 12 parts of the composite thixotropic component, 0.3 parts of polyether defoamer and 0.4 parts of polyurethane leveling agent, first disperse at a high speed of 1500 r / min for 30 min, then reduce to 800 r / min and stir for 20 min to obtain component A; 55 parts of modified aliphatic polyamine curing agent (MH-2218, active hydrogen equivalent of 105 g / eq) were stirred evenly to obtain component B; Take a steel pipe support substrate and pre-treat its surface by sandblasting to remove rust and degreasing with anhydrous ethanol. Before coating, prepare and use component A and component B immediately and mix them evenly. Apply the mixture in three coats to the surface of the pre-treated steel pipe support substrate. Before each coat, weigh and mix component A and component B according to the required amount for that coat. Use the mixture within 30 minutes. Control the wet film thickness of each coat to 70 μm and leave a 50-minute interval between coats. After curing at room temperature for 7 days, bake at 60℃ for 3 hours for post-curing to form an anti-corrosion coating and obtain a corrosion-resistant pipe support.
[0032] Example 4 A method for preparing a corrosion-resistant pipe support includes the following steps: (1) According to the weight parts, 100 parts of anhydrous ethanol and 4 parts of deionized water are mixed evenly, 10 parts of mica powder with a flake diameter of 15-20 μm are added, and after stirring and dispersing evenly, 0.5 parts of aminosilane coupling agent KH-792 are added. The mixture is stirred and reacted at 65℃ for 2h. After the reaction is completed, the mixture is centrifuged at 4000r / min, washed 3 times with anhydrous ethanol, and dried at 80℃ for 4h to obtain aminosilane modified mica powder.
[0033] (2) 10 parts of montmorillonite with a flake diameter of 5-15 μm were dispersed in 150 parts of deionized water. Under stirring conditions at 48°C, 72 parts of 0.5 mol / L zinc nitrate solution and 48 parts of 0.5 mol / L disodium hydrogen phosphate solution were added slowly and synchronously from two dropper ports to the above montmorillonite aqueous dispersion system, so that the molar ratio of zinc ions to phosphate was 3:2. During the droppering process, the pH of the reaction system was adjusted and maintained at 5.5-6.5 with 0.1 mol / L dilute sodium hydroxide solution. After the droppering was completed, the reaction was stirred at 48°C for 1.5 h to obtain zinc phosphate / montmorillonite precipitate loaded slurry. Then, 3.5 parts of hexadecyltrimethylammonium bromide were added to the slurry and the reaction was stirred at 75°C for 2.5 h. The mixture was centrifuged at 4000 r / min, washed with deionized water until the filtrate was neutral, and dried at 90°C for 8 h to obtain composite corrosion inhibitor powder.
[0034] (3) Disperse 10 parts of fumed nano silica with a particle size of 20-40 nm in 160 parts of anhydrous ethanol, add 6 parts of deionized water, stir and disperse evenly, then add 1.2 parts of octyltrimethoxysilane, stir and react at 70 °C for 2.5 h, centrifuge at 5000 r / min, and dry at 100 °C for 3 h to obtain hydrophobic modified nano silica.
[0035] (4) Add 2 parts of the hydrophobic modified nano silica and 4 parts of talc with a sheet diameter of 1-5 μm to 10 parts of butyl glycidyl ether resin dilution, and stir and disperse at 1000 r / min for 40 min to obtain a composite thixotropic component.
[0036] (5) Mix 100 parts of bisphenol A type epoxy resin E-51 (epoxy equivalent 190 g / eq), 15 parts of the aminosilane modified mica powder, 6 parts of the composite corrosion inhibitor powder, 15 parts of the composite thixotropic component, 0.5 parts of polyether defoamer and 0.8 parts of polyurethane leveling agent, first disperse at a high speed of 1500 r / min for 30 min, then reduce to 800 r / min and stir for 20 min to obtain component A; 55 parts of modified aliphatic polyamine curing agent (MH-2218, active hydrogen equivalent of 105 g / eq) were stirred evenly to obtain component B; Take a steel pipe support substrate and pre-treat its surface by sandblasting to remove rust and degreasing with anhydrous ethanol. Before coating, prepare and use component A and component B immediately and mix them evenly. Apply the mixture in three coats to the surface of the pre-treated steel pipe support substrate. Before each coat, weigh and mix component A and component B according to the required amount for that coat. Use the mixture within 30 minutes. Control the wet film thickness of each coat to 70 μm and leave a 50-minute interval between coats. After curing at room temperature for 7 days, bake at 60℃ for 3 hours for post-curing to form an anti-corrosion coating and obtain a corrosion-resistant pipe support.
[0037] Example 5 A method for preparing a corrosion-resistant pipe support includes the following steps: (1) According to the weight parts, 100 parts of anhydrous ethanol and 4 parts of deionized water are mixed evenly, 10 parts of mica powder with a flake diameter of 15-20 μm are added, and after stirring and dispersing evenly, 0.1 parts of aminosilane coupling agent KH-792 are added. The mixture is stirred and reacted at 55℃ for 2h. After the reaction is completed, the mixture is centrifuged at 4000r / min, washed 3 times with anhydrous ethanol, and dried at 80℃ for 4h to obtain aminosilane modified mica powder.
[0038] (2) 10 parts of montmorillonite with a flake diameter of 5-15 μm were dispersed in 150 parts of deionized water. Under stirring conditions at 48°C, 72 parts of 0.5 mol / L zinc nitrate solution and 48 parts of 0.5 mol / L disodium hydrogen phosphate solution were added slowly and synchronously from two dropper ports to the above montmorillonite aqueous dispersion system, so that the molar ratio of zinc ions to phosphate was 3:2. During the droppering process, the pH of the reaction system was adjusted and maintained at 5.5-6.5 with 0.1 mol / L dilute sodium hydroxide solution. After the droppering was completed, the reaction was stirred at 48°C for 1.5 h to obtain zinc phosphate / montmorillonite precipitate loaded slurry. Then, 3.5 parts of hexadecyltrimethylammonium bromide were added to the slurry and the reaction was stirred at 75°C for 2.5 h. The mixture was centrifuged at 4000 r / min, washed with deionized water until the filtrate was neutral, and dried at 90°C for 8 h to obtain composite corrosion inhibitor powder.
[0039] (3) Disperse 10 parts of fumed nano silica with a particle size of 20-40 nm in 160 parts of anhydrous ethanol, add 6 parts of deionized water, stir and disperse evenly, then add 0.8 parts of octyltrimethoxysilane, stir and react at 60 °C for 2.5 h, centrifuge at 5000 r / min, and dry at 100 °C for 3 h to obtain hydrophobic modified nano silica.
[0040] (4) Add 2 parts of the hydrophobic modified nano silica and 2 parts of talc with a sheet diameter of 1-5 μm to 10 parts of butyl glycidyl ether resin dilution, and stir and disperse at 1000 r / min for 40 min to obtain a composite thixotropic component.
[0041] (5) Mix 100 parts of bisphenol A type epoxy resin E-51 (epoxy equivalent 190 g / eq), 10 parts of the aminosilane modified mica powder, 3 parts of the composite corrosion inhibitor powder, 10 parts of the composite thixotropic component, 0.1 parts of polyether defoamer and 0.1 parts of polyurethane leveling agent, first disperse at a high speed of 1500 r / min for 30 min, then reduce to 800 r / min and stir for 20 min to obtain component A; 55 parts of modified aliphatic polyamine curing agent (MH-2218, active hydrogen equivalent of 105 g / eq) were stirred evenly to obtain component B; Take a steel pipe support substrate and pre-treat its surface by sandblasting to remove rust and degreasing with anhydrous ethanol. Before coating, prepare and use component A and component B immediately and mix them evenly. Apply the mixture in three coats to the surface of the pre-treated steel pipe support substrate. Before each coat, weigh and mix component A and component B according to the required amount for that coat. Use the mixture within 30 minutes. Control the wet film thickness of each coat to 70 μm and leave a 50-minute interval between coats. After curing at room temperature for 7 days, bake at 60℃ for 3 hours for post-curing to form an anti-corrosion coating and obtain a corrosion-resistant pipe support.
[0042] Comparative Example 1: Compared with Example 4, the only difference is that in step (1), the mica powder is not modified with an aminosilane coupling agent. That is, in step (5), an equal amount of unmodified mica powder is directly used to replace the aminosilane-modified mica powder. The remaining steps and raw materials are the same as in Example 4.
[0043] Comparative Example 2: Compared with Example 4, the only difference is that aminosilane-modified mica powder is not added in step (5) (i.e., this component is omitted and not replaced in equal amounts), and the other steps and raw materials are the same as in Example 4.
[0044] Comparative Example 3: Compared with Example 4, the only difference is that hexadecyltrimethylammonium bromide is not added in step (2) for organic intercalation modification, that is, zinc phosphate / montmorillonite precipitated loaded powder without CTAB intercalation is used to replace the composite corrosion inhibitor powder. The remaining steps and raw materials are the same as in Example 4.
[0045] Comparative Example 4: Compared with Example 4, the only difference is that zinc phosphate is not loaded in step (2), that is, an equal amount of organic montmorillonite modified only by hexadecyltrimethylammonium bromide is used to replace the composite corrosion inhibitor powder. The remaining steps and raw materials are the same as in Example 4.
[0046] Comparative Example 5: Compared with Example 4, the only difference is that the composite corrosion inhibitor powder is not added in step (5) (i.e., the component is omitted and not replaced in equal amounts), while the other steps and raw materials are the same as in Example 4.
[0047] Comparative Example 6: Compared with Example 4, the only difference is that hydrophobic modified nano-silica is not added in (4), that is, the composite thixotropic component is only prepared by equal amounts of flake talc powder and butyl glycidyl ether resin diluent, and the other steps and raw materials are the same as in Example 4.
[0048] Comparative Example 7: Compared with Example 4, the only difference is that flake talc is not added in step (4), that is, the composite thixotropic component is only prepared by equal amounts of hydrophobically modified nano silica and butyl glycidyl ether resin diluent. The remaining steps and raw materials are the same as in Example 4.
[0049] Comparative Example 8: Compared with Example 4, the only difference is that in step (3), the nano-silica is not modified with octyltrimethoxysilane hydrophobic modification. That is, an equal amount of unmodified fumed nano-silica and flake talc are used to prepare a composite thixotropic component. The remaining steps and raw materials are the same as in Example 4.
[0050] Comparative Example 9: Compared with Example 4, the only difference is that the composite thixotropic component is not added in step (5) (i.e., the component is omitted and not replaced in equal amounts), while the other steps and raw materials are the same as in Example 4.
[0051] Comparative Example 10: Compared with Example 4, the only difference is that in step (5), aminosilane-modified mica powder and composite corrosion inhibitor powder are not added at the same time, and only the composite thixotropic component is retained. The remaining steps and raw materials are the same as in Example 4.
[0052] Performance testing: (1) Neutral salt spray test tolerance time: Refer to GB / T 10125—2021 (ISO 9227:2017) "Artificial atmosphere corrosion test - salt spray test", scratch the sample coated with anti-corrosion coating with a sharp knife until the diagonal cross marks (cross marks) are made on the substrate. Place it in the salt spray test chamber and spray continuously with 5% neutral sodium chloride solution (pH=6.5~7.2) at 35℃. Observe the rust, blistering and peeling on both sides of the scratch and the unscratched area of the sample every 24 hours. Record the cumulative spray time corresponding to when the single-sided corrosion width of the scratch exceeds 2mm or obvious rust spots and blistering appear in the unscratched area. The longer the time, the better the long-term corrosion resistance of the coating.
[0053] (2) Adhesion (pull-off method): Refer to GB / T 5210—2006 (ISO 4624) "Paints and varnishes - pull-off test for adhesion". Use a two-component adhesive to bond the test column to the coating surface. After curing, apply a vertical pull force with an adhesion tester until the coating is pulled off and destroyed. Record the tensile stress (MPa) at the point of failure. The higher the value, the higher the bonding strength between the coating and the substrate and the interior of the coating.
[0054] (3) Pencil hardness: Refer to GB / T 6739—2022 "Determination of paint film hardness by pencil method for paints and varnishes". A set of pencils with known hardness are used to scrape the coating surface under a constant load (750g) and a 45° angle. The highest pencil hardness value corresponding to the coating without being scratched is used to characterize the surface hardness of the coating.
[0055] (4) Electrochemical impedance spectroscopy (EIS) of the coating: Using an electrochemical workstation, with the coated sample as the working electrode, a saturated calomel electrode as the reference electrode, and a platinum electrode as the auxiliary electrode, the sample was immersed in a 3.5% sodium chloride solution for 30 days before electrochemical impedance spectroscopy (EIS) was performed. The scanning frequency range was 10. 5 ~10 -2 Record the impedance magnitude |Z| at 0.01 Hz. 0.01 Hz (Ω·cm) 2 The larger the value, the stronger the coating's ability to shield and inhibit corrosion.
[0056] (5) Storage stability (settling degree): Refer to GB / T 6753.3—1986 "Test method for storage stability of coatings", take component A and put it into a sealed container. After storing it in an oven at 50℃ for 30 days, take it out and use a stirring rod to insert into the bottom of the container to check the sedimentation and agglomeration of pigments and fillers. The evaluation is based on 0 to 10. A grade of 10 indicates no sedimentation, no resistance when inserting the stirring rod and no agglomeration. The higher the grade, the better the storage stability against sedimentation and stratification of pigments and fillers.
[0057] Table 1: Compared with Example 4, Comparative Example 1 (mica powder without aminosilane modification) and Comparative Example 2 (without mica powder) showed a significant decrease in adhesion and salt spray tolerance time, indicating that aminosilane-modified mica powder not only improved interfacial adhesion through surface amino-epoxy bonding, but also delayed the penetration of corrosive media by constructing a physical barrier through the directional arrangement of lamellar layers. The adhesion of Comparative Example 1 (7.2 MPa) was significantly lower than that of Comparative Example 2 (8.6 MPa), further illustrating that the unmodified mica powder had poor interfacial bonding with the resin and instead formed a weak interface.
[0058] The salt spray tolerance time and impedance modulus of Comparative Example 3 (without CTAB intercalation), Comparative Example 4 (without zinc phosphate loading), and Comparative Example 5 (without composite corrosion inhibitor powder) decreased sequentially, with Comparative Example 5 showing the largest decrease. This indicates that the corrosion inhibition activity of zinc phosphate, the slow release of montmorillonite loading, and the hydrophobic regulation of CTAB intercalation are all necessary to achieve long-term slow-release passivation, and none of them can be omitted.
[0059] The storage stability sedimentation grades of Comparative Example 6 (without hydrophobic nano-silica), Comparative Example 7 (without flake talc), Comparative Example 8 (nano-silica without hydrophobic modification), and Comparative Example 9 (without composite thixotropic components) decreased significantly, especially Comparative Example 9, which only reached grade 3 (component A showed severe sedimentation and agglomeration after heat storage). Although Comparative Example 9 still contained aminosilane-modified mica powder and composite corrosion inhibitor powder, its salt spray tolerance time (1104 h) and impedance modulus (9.0 × 10⁻⁶) were significantly improved. 8 Ω·cm 2 The corrosion resistance of Example 6 was still higher than that of Example 5, which lacked corrosion inhibition function. However, due to severe sedimentation and stratification of pigments and fillers and uneven distribution of shielding and corrosion-inhibiting components in the coating, its corrosion resistance was significantly lower than that of Example 4, which had a uniform component distribution. This indicates that although the gradient anchoring network constructed by hydrophobic modified nano-silica and flake talc does not directly provide shielding or corrosion inhibition function, it ensures the uniform synergy of the two anti-corrosion mechanisms in the coating by inhibiting the sedimentation and stratification of pigments and fillers. The comparison between Comparative Example 6 and Comparative Example 7 also shows that the anti-settling effect of using either alone is inferior to that of the combination of the two (Example 4).
[0060] Comparative Example 10 (containing only the composite thixotropic component, excluding shielding and corrosion-inhibiting pigments) had a salt spray tolerance time of only 456 hours and an impedance modulus of only 4.5 × 10⁻⁶. 7 Ω·cm 2 The level is close to that of unmodified pure epoxy coatings, which proves the decisive contribution of the dual-functional components of shielding and corrosion inhibition to the corrosion resistance of the coating.
[0061] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the essence and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a corrosion-resistant pipe support, characterized in that, Includes the following steps: (1) Mica powder is reacted with an aminosilane coupling agent to obtain aminosilane modified mica powder; the aminosilane coupling agent is aminosilane coupling agent KH-792; the reaction temperature is controlled at 55-65℃; the mica powder has a flake diameter of 15-25μm; the mass ratio of mica powder to aminosilane coupling agent is 10:(0.1-0.5); (2) Montmorillonite is dispersed in a solvent, and zinc salt solution and phosphate solution are added simultaneously for in-situ precipitation reaction. Then, a cationic surfactant is added for reaction to obtain composite corrosion inhibitor powder. The zinc salt solution is zinc nitrate solution, and the phosphate solution is disodium hydrogen phosphate solution. The cationic surfactant includes hexadecyltrimethylammonium bromide. The particle size of the montmorillonite is 5-15 μm. During the simultaneous addition of zinc salt solution and phosphate solution, the molar ratio of zinc ions to phosphate is controlled to be 3:2, and the pH of the reaction system is adjusted to 5.5-6.5 during the dropwise addition. (3) React nano-silica with a hydrophobic silane coupling agent to obtain hydrophobic modified nano-silica; the hydrophobic silane coupling agent is octyltrimethoxysilane; the reaction temperature is controlled at 60-70℃, the nano-silica particle size is 20-40nm; the mass ratio of nano-silica to octyltrimethoxysilane is 10:(0.8-1.2); (4) The hydrophobic modified nano silica and flake talc are added to a butyl glycidyl ether resin diluent and dispersed evenly to obtain a composite thixotropic component; the flake diameter of the flake talc is 1-5 μm; the mass ratio of the hydrophobic modified nano silica to the flake talc is 1:(1-2). The aminosilane-modified mica powder, the composite corrosion-inhibiting powder, the composite thixotropic component, and epoxy resin are mixed to form component A. Component B, which contains a curing agent, is mixed with component A and then coated onto the surface of the pipe support substrate and cured to obtain the corrosion-resistant pipe support. By weight, the raw material ratio of component A includes: 100 parts epoxy resin, 10-15 parts aminosilane modified mica powder, 3-6 parts composite corrosion inhibitor powder, and 10-15 parts composite thixotropic component; component A also includes 0.1-0.5 parts defoamer and 0.1-0.8 parts leveling agent; before coating the surface of the pipe support substrate, a pretreatment process of removing rust and / or oil from the surface of the pipe support substrate is also included.
2. A corrosion-resistant pipe support, characterized in that, It is prepared by the method described in claim 1.
Citation Information
Patent Citations
Silane coupling agent modified filler and preparation method of corrosion-resistant impervious epoxy composite coating thereof
CN121271300A
